FINANCIAL STABILITY OF THE INSURANCE MARKET OF DEVELOPED COUNTRIES AND SPECIFIC FEATURES OF ITS PROVISION - Hakberdiyev Bekzod Uktamovich (European Science Publishing, 2024)
This article analyzes the financial stability of the insurance market of developed countries, studies the scientific and theoretical views of foreign and domestic economists on the development of the insurance market and ensuring the financial stability of insurance companies. It also covers the mechanisms used in the development of the insurance market of developed countries and the specific features of the insurance market of foreign countries. In addition, having studied the financial stability of the insurance market of foreign countries, practical conclusions and theoretical recommendations are formulated for its application to insurance companies of Uzbekistan.
Keywords: Financial stability, insurance mechanisms, insurance products, insurance companies, insurance activities, ensuring stability, financial resources, investments, insurance market of developed countries.